OTOLOGICAL TRAUMA:: AN EXPERIENCE AT CMH PESHAWER: Otological Trauma - Ayub, Major Zeeshan; Qayyum, Asad; Najam, Atif; Khan, Jehangir; Tariq, Muhammad (Pakistan Armed Forces Medical Journal, 2012)
Objective: To study the pattern of otological trauma sustained by troops serving in Operation AI Mezan. Design: A cross sectional study. Place and Duration: Department of ENT CMH Peshawar. Data collected from hospital admission and discharge register and ENT OPD register from December 2008 to September 2010. Patients and Methods: Data of all patients of otological trauma was recorded. Nature of otological injuries was recorded along with relevant investigations and the data was studied. Results: Tympanic membrane damage is the most common otological injury observed among cases of ear trauma. Conclusion: All patients of blast trauma should have otological assessment and audiometry